role of alternative oxidase in modulating carbon use efficiency and growth during macronutrient stress in tobacco cells - Sieger, Stephen M; Kristensen, Brian K; Robson, Christine A; Amirsadeghi, Sasan; Eng, Edward W. Y; Abdel-Mesih, Amal; Møller, Ian M; Vanlerberghe, Greg C (Journal of experimental botany, 2005)
When wild-type (wt) tobacco (Nicotiana tabacum cv. Petit Havana SR1) cells are grown under macronutrient (P or N) limitation, they induce large amounts of alternative oxidase (AOX), which constitutes a non-energy-conserving branch of the respiratory electron transport chain. To investigate the significance of AOX induction, wt cells were compared with transgenic (AS8) cells lacking AOX. Under nutrient limitation, growth of wt cell cultures was dramatically reduced and carbon use efficiency (g cell dry weight gain g⁻¹ sugar consumed) decreased by 42-63%. However, the growth of AS8 was only moderately reduced by the nutrient deficiencies and carbon use efficiency values remained the same as under nutrient-sufficient conditions. As a result, the nutrient limitations more severely compromised the tissue nutrient status (P or N) of AS8 than wt cells. Northern analyses and a comparison of the mitochondrial protein profiles of wt and AS8 cells indicated that the lack of AOX in AS8 under P limitation was associated with increased levels of proteins commonly associated with oxidative stress and/or stress injury. Also, the level of electron transport chain components was consistently reduced in AS8 while tricarboxylic acid cycle enzymes did not show a universal trend in abundance in comparison to the wt. Alternatively, the lack of AOX in AS8 cells under N limitation resulted in enhanced carbohydrate accumulation. It is concluded that AOX respiration provides an important general mechanism by which plant cells can modulate their growth in response to nutrient availability and that AOX also has nutrient-specific roles in maintaining cellular redox and carbon balance.